Technological features of forming regular micro reliefs on conical surfaces - Dzyura, V.O.; Kyryk, S.S. (Problems of Tribology, 2026)
The paper examines the technological features of schemes for forming regular micro reliefs on conical surfaces. A classification of these formation schemes is proposed according to the regularity of the generated micro relief and its geometric parameters. A set of possible groove configurations of the formed micro relief has been obtained, comprising 54 variants of geometric property combinations that integrate the shape of the axial line of the micro relief grooves, the pattern of variation of the groove geometric parameters, and the groove profile itself. The specific characteristics of each technological scheme are analyzed, and the principal analytical relationships are derived that determine the interdependence between the geometric parameters defining the shape of the micro relief groove elements-namely the pitch (Tk) and the amplitude (Ag); the groove arrangement parameter – the center-to-center spacing (So); and the parameters of the conical surface, including the cone angle (αс) and the length of the axial line of the regular micro irregularities formed on the conical surface. The obtained relationships make it possible to ensure the regularity of the micro relief groove elements and to form a micro relief with the required geometric parameters. It has been established that the determination of the length of the helical line on the conical surface forms the basis for further calculations of the groove elements arranged along this line.